The joy of flying: Efficient airport PPP contracts. (August 2018) - Engel, Eduardo; Fischer, Ronald; Galetovic, Alexander
Highlights: Airport PPPs have become common. Optimal contract for an airport PPP with aeronautical, non-aeronautical revenues. Cases: Exogenous demand and a special case with endogenous demand. Contracts provide optimal incentives to efficient effort. A special case of this contract has been implemented in airports in Chile. Abstract: We derive the optimal concession contract for an airport where the concessionaire's effort impacts either non-aeronautical revenue (shops, restaurants, parking lots and hotels) or aeronautical revenues (passenger and airline fees). Our first model assumes that demand for the infrastructure is exogenous whereas demand for non-aeronautical services depends both on passenger flow and on the concessionaire's effort and diligence. We show that the optimal principal-agent contract separates exogenous and endogenous risks. First, the term of the concession varies inversely with passenger flow, so that the concessionaire bears no exogenous demand risk. Second, the concessionaire bears part or all of non-aeronautical risk, which fosters effort. We also study a model where the concessionaire's effort affects demand for aeronautical services and focus on the case where the contract includes a demand trigger for investment as an incentive. Both optimal contracts can be implemented with a Present-Value-of-Revenue (PVR) auction in which firms bid on the present value of aeronautical revenue and the concession ends when the bid is collected. PVR auctions have been used to auction airport PPP contracts in Chile, and demand triggers for investment have been used both in Brazil and Chile.